Relationship between the workplace environments with the level of employees productivity in Pejabat Agama Daerah Besut / Nor Hidayah Mohmd Salleh - Mohmd Salleh, Nor Hidayah (Faculty of Business and Management, 2017)
The final report project was carried out in order to fulfill the requirement of the Academic project (ASM662). The study was conducted at the Pejabat Agama Daerah Besut. There are three main objectives is to identify the workplace environment features in company, then to determine the level of employcc productivity in thc company and to investigate the relationship between workplace environmental features and the level employees productivity. By referring to Krejcie and Morgan table ( InO), the scopes arc focused on 60 number of population. The sample sizes taken are 52 people are referred to the sample size for a given population. The sampling technique used is simple random sampling. The data was analyzed and interpreted using SPSS software. From the overall findings, it can be concludc that employees at Pejabat Agama Daerah Besut are well performed and totally agreed about thc environmcnt at the office to make sure their job satisfaction will be increase. The morc cmployees be able to know more details about the physical component at the office slIch as space planning, environment, colors to increase productivity at the office and highest performance.